Popia Pisang Cokelat: Inovasi Camilan Kekinian Berbasis Pangan Lokal untuk Meningkatkan Nilai Ekonomis Produk Olahan Pisang - Wahyu Muh. Syata; Muhammad Juwantho Lewa; Murni Nia; Murniati Murniati; Jumatin Jumatin; Hasniah Hasniah; Fitra Ramadani; A. Amaliah (Indo Publishing, 2026)
he shifting lifestyle of students towards practical and instant snacks often neglects nutritional aspects. This community service activity aims to create an innovative, healthy, and economically valuable banana-based snack called